Theoretical and experimental studies of 161Tb production as a new therapeutic radionuclide at Tehran Research Reactor - Mehdi Sharifi; Hassan yousefnia; Ali Bahrami Samani; Amirreza Jalilian; Samaneh Zolghadri; Mohammad GhanadiMaragheh (مجله علوم و فنون هسته‌ای, 2015)
Because of the suitable decay characteristics of terbium-161 (161Tb), it is a promising radioisotope for development of new therapeutic complexes and also a good alternative to 177Lu. In this study, the production routes of 161Tb are evaluated by both theoretical and experimental methods. In the theoretical approach the chain decay equations are solved and the activity of the radionuclide and all of the other products are obtained by imposing constant values in the equations. The main route for the 161Tb production is the 160Gd(n,γ)161Gd (β-)161Tb reaction as an indirect production method. In this method, natural or enriched gadolinium can be used. For the 161Tb production, 1 mg of natural gadolinium is irradiated at the Tehran Research Reactor, using thermal neutron flux of 3×1013 cm-2 s-1 for 34 hours. The activity of each product is evaluated by means of gamma spectrometry. The results show that about 0.11 mCi of 161Tb is produced in this condition. Due to confirmation of the calculations with experiments, it can be concluded that production of about 100 mCi of 161Tb is possible by a long time irradiation of 10 mg of enriched 160Gd.